1998
DOI: 10.1115/1.2841776
|View full text |Cite
|
Sign up to set email alerts
|

Inner Workings of Aerodynamic Sweep

Abstract: The recent trend in using aerodynamic sweep to improve the performance of transonic blading has been one of the more significant technological evolutions for compression components in turbomachinery. This paper reports on the experimental and analytical assessment of the pay-off derived from both aft and forward sweep technology with respect to aerodynamic performance and stability. The single-stage experimental investigation includes two aft-swept rotors with varying degree and type of aerodynamic sweep and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(25 citation statements)
references
References 14 publications
1
23
1
Order By: Relevance
“…The overall loss then is determined by the secondary Figure 5 Mass average out §ow angles: 1 ¡ baseline; and 2 ¡ backward §ow losses. This may be the reason why some investigations [7,10] reported signi¦cant loss reductions and others [12] did not in applying the sweep in airfoils. The isentropic Mach number distributions shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The overall loss then is determined by the secondary Figure 5 Mass average out §ow angles: 1 ¡ baseline; and 2 ¡ backward §ow losses. This may be the reason why some investigations [7,10] reported signi¦cant loss reductions and others [12] did not in applying the sweep in airfoils. The isentropic Mach number distributions shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Forward sweep modifies the flow structure in low speed axial compressors by the following: (1) Reducing the blade loading in the frontal area near the tip region, which results in flow near the leading edge becoming more tolerant to the changes in incidence and reduced tip leakage in this area. (2) Modification in the movement of centrifuged blade boundary layer which will not result in accumulation of low energy fluid near tip sections to cause separation and formation of stall cells at lower flow coefficients [1,4,5]. Major sweep effects in compressor rotors are thus found above the mid span, particularly near the tip, where the flow leaking from the finite tip gap already has its own influence.…”
Section: Introductionmentioning
confidence: 99%
“…Deliberate use of sweep in subsonic blade rows is found to improve the operating range and efficiency characteristics, while in transonic environment it is due to significant changes in the shock structure to reduce shock-related losses [2,3]. Leading edge sweep is employed in designs intended to modify the local blade loading conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1998, Wadia et al [4] reported the experimental and analytical assessment of the effect of aft-and forward sweep technology of transonic fan or compressor rotors. They concluded that forward sweep can result in improvements in both efficiency and stall margin and the better performance of the forward-swept rotor is attributed to the reduced shock/boundary layer interaction resulting from reduced axial flow diffusion.…”
Section: Introductionmentioning
confidence: 99%